2022
DOI: 10.1590/1413-81232022274.03372021
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in the consumption of minimally processed and ultra-processed foods in Brazilian adolescents

Abstract: In this study, we evaluated socioeconomic inequalities in the consumption of in natura/minimally processed and ultra-processed foods among adolescents. We used data from the Brazilian National Survey of School Health (PeNSE), 2015. According to the self-reported consumption of beans, vegetables and fruits, a score of in natura/minimally processed foods was generated (0-21 points). Sodas, sweets, instant noodles, and ultra-processed meat were used for the score of ultra-processed foods (0-21 points). Equality i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
7
0
3
Order By: Relevance
“…In our study, the most significant number of respondents were female (58.9%), as with other surveys, since females tend to care more about health and food and are more available to answer questionnaires [ 7 , 8 , 9 , 33 , 34 , 35 , 36 , 37 ]. Studies assessing consumer food choices have shown that women typically: assume responsibility for managing the household pantry; keeping the family nourished and healthy; being concerned with the feeding of children; being more concerned with health and aspects related to the nutritional value of food, possibly justifying, in such a way, the participation of women in research related to food and nutrition [ 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 70%
“…In our study, the most significant number of respondents were female (58.9%), as with other surveys, since females tend to care more about health and food and are more available to answer questionnaires [ 7 , 8 , 9 , 33 , 34 , 35 , 36 , 37 ]. Studies assessing consumer food choices have shown that women typically: assume responsibility for managing the household pantry; keeping the family nourished and healthy; being concerned with the feeding of children; being more concerned with health and aspects related to the nutritional value of food, possibly justifying, in such a way, the participation of women in research related to food and nutrition [ 38 , 39 , 40 ].…”
Section: Discussionsupporting
confidence: 70%
“…A survey carried out with 50 adolescents from a private school in Minas Gerais, Brazil, identified that 84.6% of them allocated half of the financial resources of their purchases to UPFs [ 24 ]. Another study, carried out with data from the 2015 National School Health Survey, which was multicentric and included public and private schools, revealed that adolescents from higher socioeconomic levels consumed more unprocessed foods, but also UPFs when compared to those from lower socioeconomic levels [ 25 ]. These results demonstrate that UPF consumption is significantly present in the diet of the Brazilian school-age population, regardless of social, economic, and geographical issues.…”
Section: Discussionmentioning
confidence: 99%
“…Nota-se que a associação da renda familiar com o consumo alimentar no Brasil ainda apresenta um padrão alimentar contraditório 14,15,17,41 . Em recente revisão 39 que analisou as iniquidades sociais no consumo alimentar no Brasil, destacase que famílias com maior renda possuem uma alimentação mais diversificada e rica em nutrientes, mas também, tem alto consumo de AUP.…”
Section: Discussionunclassified
“…A ingestão dos AUP tem aumentado ao longo dos anos [3][4][5][6] e, entre adolescentes brasileiros, tem sido associado a dependência administrativa da escola [10][11][12][13] ; à renda familiar 6,14,15 e o nível de educação dos pais 14 ; inatividade física 6,16 ; comportamento sedentário, especialmente em indivíduos com alto tempo de tela 13,16,17 ; culminando em excesso de peso 3,4,18 , síndrome metabólica 19 e alterações no perfil lipídico 20 e na pressão arterial 21 . Dados similares foram observados na literatura internacional 22,23 .…”
Section: Introductionunclassified
See 1 more Smart Citation